Prototype Alat Pengusir Hama Burung Pipit Otomatis Berbasis Arduino Menggunakan Sensor PIR (Passive Infra Red) - Saputra, Fajar Sidik Dwi; Nasirudin, Mohamad (Exact Papers in Compilation (EPiC), 2022)
Pests have long been a problem for farmers in the pre-harvest period. So with that, the author has the idea to make an Arduino-based automatic bird repellent using a PIR sensor. Because according to the author's assumption they only need to put this tool in the field, which will later be connected to an Arduino circuit that uses a PIR sensor as an input intermediary. Later the sensor will send a signal to the servo if the sensor detects an intruder who enters the rice field area. Then the intruder, which is a sparrow, will be surprised or scared because of the movement made by the servo. And the birds will fly away from the rice plants. So the conclusion of all the projects made is to meet the specifications that have been planned by the author in terms of Software and Hardware.